2023
DOI: 10.1186/s13287-023-03364-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential advantages of genetically modified mesenchymal stem cells in the treatment of acute and chronic liver diseases

Abstract: Liver damage caused by toxicity can lead to various severe conditions, such as acute liver failure (ALF), fibrogenesis, and cirrhosis. Among these, liver cirrhosis (LC) is recognized as the leading cause of liver-related deaths globally. Unfortunately, patients with progressive cirrhosis are often on a waiting list, with limited donor organs, postoperative complications, immune system side effects, and high financial costs being some of the factors restricting transplantation. Although the liver has some capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 117 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…But in the last decade, mounting evidence has shown that membrane vesicles are important messengers in intercellular communication. Exosomes have been the most studied of these vesicles and are well-characterized [ 7 9 ].…”
Section: Overview Of Exosomes (Contents Biogenesis and Uptake)mentioning
confidence: 99%
“…But in the last decade, mounting evidence has shown that membrane vesicles are important messengers in intercellular communication. Exosomes have been the most studied of these vesicles and are well-characterized [ 7 9 ].…”
Section: Overview Of Exosomes (Contents Biogenesis and Uptake)mentioning
confidence: 99%